Cryo-Scanning Electron Microscopy (SEM) and Scanning Transmission Electron Microscopy (STEM)-in-SEM for Bio- and Organo-Mineral Interface Characterization in the Environment. (16th November 2017) - Wille, Guillaume; Hellal, Jennifer; Ollivier, Patrick; Richard, Annie; Burel, Agnes; Jolly, Louis; Crampon, Marc; Michel, Caroline
Abstract: Understanding biofilm interactions with surrounding substratum and pollutants/particles can benefit from the application of existing microscopy tools. Using the example of biofilm interactions with zero-valent iron nanoparticles (nZVI), this study aims to apply various approaches in biofilm preparation and labeling for fluorescent or electron microscopy and energy dispersive X-ray spectrometry (EDS) microanalysis for accurate observations. According to the targeted microscopy method, biofilms were sampled as flocs or attached biofilm, submitted to labeling using 4', 6-diamidino-2-phenylindol, lectins PNA and ConA coupled to fluorescent dye or gold nanoparticles, and prepared for observation (fixation, cross-section, freezing, ultramicrotomy). Fluorescent microscopy revealed that nZVI were embedded in the biofilm structure as aggregates but the resolution was insufficient to observe individual nZVI. Cryo-scanning electron microscopy (SEM) observations showed nZVI aggregates close to bacteria, but it was not possible to confirm direct interactions between nZVI and cell membranes. Scanning transmission electron microscopy in the SEM (STEM-in-SEM) showed that nZVI aggregates could enter the biofilm to a depth of 7–11 µ m. Bacteria were surrounded by a ring of extracellular polymeric substances (EPS) preventing direct nZVI/membrane interactions. STEM/EDS mapping revealed a co-localization of nZVI aggregates with lectins suggesting a potential role of EPS in nZVI embedding. Thus, the combination of divergent microscopy approaches is a good approach to better understand and characterize biofilm/metal interactions.